1970
DOI: 10.1104/pp.46.2.334
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin and Inhibitor Activities in the Avocado Fruit Mesocarp

Abstract: No cytokinin activity was found in methanolic mesocarp extracts after purification with petroleum ether and ethyl acetate. Cytokinin activity did appear, however, in aqueous fraction after acid hydrolysis or passage through Dowex 50 (H+) ion exchange columns. The level of this activity, the fruit growth rate, and the cell division rate were found to be positively correlated (with each other).An inhibitor to cytokinin activity in soybean callus bioassay was found in the petroleum ether fraction; this inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1971
1971
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 7 publications
1
18
0
1
Order By: Relevance
“…4) (3). They observed that while no cytokinin activity was found in the methanolic extract of avocado mesocarp, this activity, as assayed by soybeancotyledon callus, did appear in the aqueous fraction after either acid hydrolysis or passage through Dowex 50 (H+) ion exchange columns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) (3). They observed that while no cytokinin activity was found in the methanolic extract of avocado mesocarp, this activity, as assayed by soybeancotyledon callus, did appear in the aqueous fraction after either acid hydrolysis or passage through Dowex 50 (H+) ion exchange columns.…”
Section: Resultsmentioning
confidence: 99%
“…To estimate cytokinin activity, the water phase which was separated from the ethyl acetate fraction containing the ABA was passed through a Dowex column as described by Gazit and Blumenfeld (3). The appropriate eluate was dried and redissolved in methanol (70% v/v).…”
mentioning
confidence: 99%
“…Cytokinin activity was determined by the soybean callus bioassay (26), according to Gazit and Blumenfeld (11).…”
Section: Methodsmentioning
confidence: 99%
“…In several cases, only pigment changes of chlorophyll breakdown, or lycopene synthesis have been affected by these hormones (1,11,22). Blumenfeld and Gazit (6) and Gazit and Blumenfeld (17) have demonstrated the existence of gibberellins and cytokinins, respectively, in avocado fruits. They have also pointed to the possible synthesis of these hormones in the fruit, particularly in the seed coat.…”
Section: Discussionmentioning
confidence: 99%